Microbiological quality of sugarcane juice marketed in a free fair in União dos Palmares, Alagoas, Brazil - Ataíde, Clara Beatriz; Silva, Sybelle Geórgia Mesquita da; Silva, João Manoel da; Rocha, Jéssica Raimundo da; Santos, Jéssica Marcy Silva Melo; Santos, Tania Marta Carvalho dos (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
The objective of this work was to evaluate the microbiological quality of samples of sugarcane broth marketed in a fair in the State of Alagoas. Seven samples of informally traded sugarcane broth were collected at intervals of fifteen days and taken to the laboratory for analysis. The aseptically collected samples were diluted in 0.1% peptone saline solution, where 25 mL of each sample was diluted in 225 mL of this solution and inoculated into test tubes containing Lauryl Sulfate Triptose (LST) medium and an inverted Durham tube for the Presumptive tests and, subsequently, samples that formed gas were transferred to tubes containing EC medium and Brilliant Green for tests of total and thermotolerant coliforms, respectively. Yeasts were analyzed by means of inoculation in PDA medium and microscopic visualization. The detection of protozoa was done through traps made in PVC tube in Agar-water medium. The soil was analyzed by means of filtration and microscopic observation. All samples had total and thermotolerant coliforms with a maximum count of >2400 MPN/mL. The yeast count showed 8x10-6 UFC. Of the total of 21 samples, only two in the first collection showed protozoa. None of the samples showed dirt.